Advanced Energy Systems in Energy-Resilient and Zero/Positive Energy Buildings, Communities, and Districts - Hassam ur Rehman; Ala Hasan (Energies)
The pursuit of sustainable energy solutions has become a critical focus in addressing the challenges of climate change and urbanization [...]